The Workers Gardens and the Family Farming. Chile: 1930-1945 [Los Huertos Obreros y la Agricultura Familiar. Santiago de Chile: 1930-1945] - Deichler-Carrasco, C (UNIV NACL LA PLATA, FAC HUMANIDADES & CIENCIAS EDUCACION, 2018)
This article analyzes the development of workers gardens in Chile between 1930 and 1945 in the context of the debates about the problems of supply, the rise in the cost of living, and the problems associated with urban growth. The workers gardens appear as a multifactorial response to face the subsistence problems presented by the workers family, but also as production modalities that helped to mobilize a series of social values associated with a working-class model which the authorities and businessmen wanted to promote. In this respect, this article analyzes the debates that took place around the promotion of the workers gardens, the legislative proposals, as well as the actions promoted by two model companies in their area: the Compañía Manufacturera de Cartones, the Compañía Carbonífera e industrial de Lota and the Empresa Cemento El Melón. © 2018 Centro de Estudios Historico-Rurales. All rights reserved.